The role of statins in the regulation of breast and colorectal cancer and future directions - Dang, Yexing; Zhang, Yu; Wang, Zhihao (Frontiers in Pharmacology, 2025)
Statins, widely recognized as a cornerstone in the prevention of cardiovascular diseases, have garnered increasing attention in oncology due to their pleiotropic effects, particularly their potential roles in regulating breast and colorectal cancer. Emerging evidence suggests that statins may exert anticancer effects through multiple mechanisms, including the mitochondrial apoptosis pathway, the LKB1-AMPK-p38MAPK-p53-survivin signaling cascade, inhibition of the mevalonate pathway, modulation of the EGFR/RhoA and IGF-1 signaling pathways, and regulation of the BMP/SMAD4 signaling pathway. However, significant heterogeneity exists in the reported anticancer effects of statins, likely due to variations in statin type (lipophilic vs hydrophilic), dosage, treatment duration, and population-specific characteristics. These factors contribute to inconsistencies in study outcomes. Additionally, while combination therapies incorporating statins with chemotherapy and immunotherapy have demonstrated synergistic effects in certain studies, their clinical utility remains to be fully established. Nevertheless, current evidence suggests that statins may have a potential role in reducing breast and colorectal cancer-related mortality. Future research should prioritize elucidating their precise molecular mechanisms, defining dose–response relationships, developing personalized treatment strategies within the framework of precision medicine, and validating their efficacy through large-scale, long-term prospective studies. These efforts will provide a more robust scientific foundation for the clinical application of statins in oncology. This review systematically explores the role of statins in breast and colorectal cancer regulation, covering clinical evidence, underlying biological mechanisms, pharmacological distinctions, synergistic therapeutic potential, and translational medicine prospects.